RelQ Mediates the Expression of β-Lactam Resistance in Methicillin-Resistant Staphylococcus aureus - Bhawini, Ajita; Pandey, Parul; Dubey, Ashutosh Prakash; Zehra, Aafreen; Nath, Gopal; Mishra, Mukti Nath (Frontiers in Microbiology, 2019)
An induced stringent response, which is established by an increased level of (p)ppGpp, is required for the expression of β-lactam resistance in methicillin-resistant Staphylococcus aureus (MRSA). However, it is not clear whether RSH (enzyme mediating stringent response to amino acid starvation) or small alarmone synthetases (SASs) are involved in the maintenance of (p)ppGpp level in response to β-lactams. Since the S. aureus genome encodes two active SASs (RelP and RelQ), their contribution to the expression of β-lactam resistance in MRSA was investigated. It was determined that relQ deletion renders community-associated MRSA (CA-MRSA) sensitive to β-lactams by negatively affecting the expression of mecA, and induction of (p)ppGpp synthesis by mupirocin bypasses the requirement of relQ for the expression of high-level β-lactam resistance. Surprisingly, relP deletion increased the level of β-lactam resistance. Such contradictory observations could be attributed to the fact that relQ promoter is 5-fold stronger than the relP and is induced by oxacillin as well as deletion of either of the SASs, while relP promoter responds only to oxacillin. The stronger promoter activity of relQ, coupled with the inducibility of the relQ promoter in response to the lack of relP, results in efficient expression of relQ in the relP-deleted background. This positively affects mecA expression and renders the ΔrelP strain highly resistant. These findings indicate an important role for RelQ in the expression of high-level β-lactam resistance in MRSA.